The Role of Intelligence Unit in Preventing Potential Motorcycle Gang Crimes (Study in Bandung Regency) - Permana, Ivonne Kartika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
In carrying out the prevention of motorcycle gang crimes, the Intelkam Unit has inhibiting factors, namely the limited budget given to carry out investigation tasks, the lack of public participation in reporting motorcycle gang actions that interfere with Kamtibmas, the lack of Unit Intelkam personnel, and the lack of member capabilities. For find out how the implementation of Bandung Police Intelligence Unit in Preventing Crimes committed by Motorcycle Gangs, then factors that influence the prevention of motorcycle gang crimes and to find out what efforts are made by the Intelkam Unit when facing obstacles in preventing crime. Method in this research descriptive method which describes based on the reality that exists and was found at the time of doing the research. This research was conducted by interview, literature study and documentation. The results showed that the Bandung Police Intelligence Unit played a role in carrying out early warning systems and early detection carried out through investigation efforts, namely by collecting information or information material, then taking security to overcome existing Kamtibmas disturbances through monitoring places. vulnerable places and the last is by raising funds to seek and obtain information to be presented to the leadership so that further it can take a policy to tackle the crime of theft with violence which is in the jurisdiction of the Bandung Police